A Journey Through Islamic Art Exhibition: Purification of Form, Ineradicable in Content - Muhammad Uzair Ismail (Wacana Seni Journal of Arts Discourse, 2024)
Throughout the years, the manifestations of Islamic art from east and west have been diverse in the formalistic aspects but united in its spiritual essence. The wide range of ornamental motifs, stylisation, placement, material, and context is constantly changing according to the current trend of the period, reflecting the historical, social-cultural and economic background it was produced. This ensues that change is inevitably bound to happen, where traditional approach in Islamic art might not be suitable to implement in the modern society due to the unavailability of precious materials and patronage as before. Despite the challenge, the “Islamic” identity in their artworks is still being discretely preserved in their expression despite implementing and combining new techniques, styles, forms, and materials with traditional approaches. This creates an asymmetrical balance that embraces change while maintaining the Islamic principle, philosophy, and spiritual allure in their artistic production where the artists design their art to be parallel and in context with modernity. However, the Islamic identity in contemporary artworks is difficult to identify and challenging to decipher as the visual expression differs significantly from traditional art forms that people are accustomed to, making it vaguely recognised and understood. This constant and dynamic flux of tolerance and acculturation is something that is being visually exhibited by the Islamic Arts Museum Malaysia (IAMM) in their special curation “A Journey Through Islamic Art” that showcases traditional and contemporary form of Islamic art in the same place. Although the curation is impressive, but the visual tension it creates invokes the mind to think deeply about what makes an Islamic art “Islamic” and what is the suitable approach to appropriately fathom and consider the art piece as a work of “Islamic art” as the physical form of calligraphy alone is not sufficient for it to be considered as “Islamic.”